Helicobacter pylori and gastro-esophageal reflux disease (GERD) - Lesmana, Murad (Universa Medicina, 2010)
Helicobacter pylori is the major cause of gastritis and duodenitis, and is responsible for the majority of gastric and duodenal ulcers. It is thought that H.pylori may have a benign influence in the prevention of reflux esophagitis and gastro-esophageal reflux disease (GERD). GERD is due to failure of the gastro-esophageal anti-reflux mechanism, thus allowing gastric acid to damage the esophageal mucosa, but the main abnormalities may also be found in the stomach and duodenum. The recently decreased prevalence of H.pylori has led to a lower incidence of duodenal ulcer and gastric carcinoma, but increasing acid secretion resulted in an increase in GERD. Eradication of H.pylori does not aggravate the symptoms of GERD and also does not induce the development of GERD in the normal population or in patients with duodenal ulcer. Pharmacological suppression of acid secretion is more effective in patients infected with H.pylori in comparison to non-infected individuals. The evidence on the efficacy of acid suppression therapy and its association with H.pylori infection is still contradictory. The sharply differing opinions regarding the role or association of H.pylori infection with GERD have not been reconciled and contradictory study results are still widespread.